Estimation of Net Premium for Flight Delay Insurance Using the Aggregate Loss Model: A Case Study of Indonesia OTAs - Husna, Azka Nurul; Hikmah, Yulial; Hikmah, Ira Rosianal (UI Scholars Hub, 2026)
Air transportation, as one of the most chosen transportation modes, is frequently susceptible to delays. Flight Delay Insurance offers a vital solution to mitigate the financial losses associated with this risk. Premium pricing is a key factor influencing the decision to purchase this insurance, particularly on Online Travel Agent (OTA) platforms where product offerings are often highly comparable. The aggregate loss method is employed herein to ascertain the net premium (or pure premium) price. The loss severity component (X) is modeled using an empirical distribution, while the loss frequency component (N) is modeled using a Negative Binomial distribution with parameters r =1.3719 and β =102.05. The resulting collective monthly pure premium is Rp 84,000,261, which constitutes 66.71% of the average monthly gross premium revenue earned by the observed OTA platform. Consequently, the pure premium per unit is determined to be Rp 45,649. This study offers a novel contribution by applying the aggregate loss model to empirical data from the Online Travel Agent (OTA) industry in Indonesia, aligned with the national passenger compensation regulatory framework to yield practically accurate premium estimations.